Inclusive Human Resources (HR) Practices, Employee Engagement, and Retention: Evidence from Diverse Workforces in Southwestern Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2026)
The increasing demand for workplace inclusivity has heightened interest in how human resource (HR) practices affect employee outcomes across diverse organizational settings. While evidence from Western contexts indicates that inclusive HR practices improve positive work attitudes, limited empirical data from Sub-Saharan Africa exists. This study examined the impact of inclusive HR practices on employee engagement and retention among diverse workforces in Southwestern Nigeria. Drawing on Social Exchange Theory and the Job Demands-Resources model, it was hypothesized that inclusive HR practices would boost engagement and decrease turnover intentions, with engagement serving as a mediator. A cross-sectional survey of 378 employees in five industries across Lagos, Oyo, and Ogun States was carried out using validated tools, including the Utrecht Work Engagement Scale. Structural equation modeling showed that inclusive HR practices significantly predicted employee engagement (β = 0.47, p < 0.001) and negatively influenced turnover intentions (β = -0.39, p < 0.001). Mediation analysis revealed that engagement partly mediated the relationship between inclusive HR practices and turnover intentions. These results suggest that inclusive HR practices foster employees’ psychological attachment to their work while lowering their desire to leave. The study advances Human Resources Management (HRM) scholarship by providing evidence from Africa on inclusivity and engagement and offers practical advice for organizations in Nigeria aiming to develop engaged and stable workforces.